The Impact of Oil Prices on State Budget Income and Expenses: Case of Azerbaijan - Humbatova, Sugra (International Journal of Energy Economics and Policy, 2023)
Since Azerbaijan is one of the oil exporting countries, its macroeconomic indicators, especially the exchange rate, the state budget are highly dependent on the oil factor. This study assessed the role of oil in the economy and the impact of the oil factor on the revenues and expenditures of the state budget of Azerbaijan in manat and dollar terms. The study covers the period 2005m03 − 2022m05. Unit root (Augmented Dickey−Fuller (ADF), Phillips−Perron (PP) and Kwiatkowski−Phillips−Schmidt−Shin (KPSS)) tests were applied to check the stationarity of variables (time series). ARDL was applied as a research method. In terms of the reliability of the obtained results, the error correction model (ECM) was used, standard tests were carried out, and the joint integration methods of FMOLS, DOLS and CCR were also applied in the evaluation. Engel−Granger and Phillips−Ouliaris tests have been used to test for cointegration interactions between variables. Short−term, long−term, and strong associations between variables were also calculated. The results of the study showed that the state budget depends on the oil and gas sector, and fluctuations in world oil prices functionally and along the chain affect oil revenues and the state budget. A different impact of oil prices (oil revenues) on the state budget in terms of manat and dollar was the devaluation of the manat, which was carried out to reduce the impact of the global financial and economic crisis on Azerbaijan. The general conclusion of the study was a recommendation to further accelerate work on the diversification of the economy and the development of the non−oil sector. The results of the conducted research can serve as a scientific basis for the economic policy of the state aimed at reducing the impact of external oil price shocks on the economy of Azerbaijan and other similar oil−exporting countries, including on the state budget, and diversifying the economy. The functional dependencies of the income and expenses of the state budget in terms of manat and dollar on world oil prices are given below.